1998
DOI: 10.1007/s004200050254
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to carbon black: a cancer risk?

Abstract: Lung cancer is one of the most serious health problems in the industrial nations and is therefore of great public and scientific interest. Although inhalative cigarette smoking is without doubt the main cause for the increasing frequency of lung cancer, during recent years there has been more and more public interest in other substances in the environment or at the work place that are assumed to be potentially carcinogenic especially due to experiences with fibrous particles such as asbestos and their effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Carbon black is produced by a number of commercial processes, one of which is thermal decomposition (combustion) of aromatic oil and coal tar distillates to produce carbon particles in the 0.01 nm-0.5 urn range, with thermal decomposition producing generally larger soot particles in the 0.12-0.5 urn range. 77 USAEHA found that Gulf War soot was a mixture of small carbon chain agglomerates of 0.1 urn and larger carbon chains composed of spherical particles 0.25 urn or greater. 78 Since Gulf War soot was produced by petroleum thermal decomposition, carbon chain agglomeration with spherical carbon particles similar to commercial carbon blacks would be expected.…”
Section: )mentioning
confidence: 99%
“…Carbon black is produced by a number of commercial processes, one of which is thermal decomposition (combustion) of aromatic oil and coal tar distillates to produce carbon particles in the 0.01 nm-0.5 urn range, with thermal decomposition producing generally larger soot particles in the 0.12-0.5 urn range. 77 USAEHA found that Gulf War soot was a mixture of small carbon chain agglomerates of 0.1 urn and larger carbon chains composed of spherical particles 0.25 urn or greater. 78 Since Gulf War soot was produced by petroleum thermal decomposition, carbon chain agglomeration with spherical carbon particles similar to commercial carbon blacks would be expected.…”
Section: )mentioning
confidence: 99%
“…These effects are attributed to a non-specific irritant effect of heavy dust exposure a BIBRA (1990), Brockmann et al (1998), Gardiner et al (1993), Gardiner (1995), IARC (1996), Kupper et al (1996), Robertson (1996), Robertson et al (1988), Szozda (1994). (Gardiner et al, 1993).…”
Section: Local Effectsmentioning
confidence: 98%
“…Effects of dust exposure were reported to include increased alterations in the upper respiratory tract, complaints of bronchitis, slight, reversible lung function changes with levels of exposure above the occupational exposure limits and slight pneumoconiotic changes depending on exposure'' (Brockmann et al, 1998).…”
Section: Local Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the amount of exposure for a person living in San Francisco, and traveling by car on 280 to work at Stanford University was expressed as DACEE (the Daily Cigarette Exposure Equivalent) being equal to 3.6 while DACEE being 1.0 represents a standard cigarette smoker (Siegmann and Siegmann 1997). In October 1995, International Agency for Research on Cancer assessed the results on a scientific basis with regard to a possible carcinogenic effect using carbon black (Brockmann et al 1998). …”
Section: Environmental and Health Aspects Of Sootmentioning
confidence: 99%